Analysis of Al-steel resistance spot welding process by developing a fully coupled multi-physics simulation model. (October 2015) - Wang, Jin; Wang, Hui-Ping; Lu, Fenggui; Carlson, Blair E.; Sigler, David R.
Abstract: This paper discusses the development of a simulation model for Al-steel resistance spot welding process, which directly couples the thermal, electrical and mechanical fields and thereby solves the equations simultaneously. For an accurate representation of strong interactions between thermal, electrical, metallurgical and mechanical phenomena in the process, the model considers temperature-dependent material properties and thermal/electrical/mechanical contact interactions at all interfaces. Its calculation accuracy is validated by comparing calculated weld nugget dimensions and electrical potentials with experimental measurements. The newly developed model provides valuable information on dynamic current flow, heat generation and transfer, nugget growth, and mechanical deformation during the process. Further on, the Al-steel intermetallic compound (IMC) thickness, which is critical to weld strength, is calculated based on the thermal history at the Al-steel contact interface and the parabolic kinetics mode of growth. The calculation is verified by experimental IMC thickness measurements. This fully coupled process simulation model provides a powerful tool for understanding the fundamental physics involved during the Al-steel resistance spot welding process and provides a significant improvement in economy over prior approaches of numerical calculation in designing welding process parameters such as electrode geometry and weld schedule prior to costly physical testing.